Pengaruh Kualitas Pelayanan, Persepsi Harga Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan - M. Zidan Supandi; Ida Bagus Eka Artika; Hj. Erviva Fariantin (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to determine the significant effect of service quality, price perception, and costumer satisfaction on custumer loyalty at the Semet Barbershop Telagawaru Village Labuapi District. The population in this study were all Semet Barbershop costumers whit a sample of 40 respondents. The research method used in this study is a quantitative approach. This research is an associative type, using the classical assumption test and multiple linear regression. The results of this study indicate that partially the service quality variabel has no significant effect on customer loyalty whit a t count of 0,007 < t table of 1,68709. Perceived price partially has no significant effect on customer loyalty whit a t count of -1,043 < t table of 1,68709. While customer satisfaction partially has a significant effect on customer loyalty whit a t count of 5,740 > t table of 1,68709. Based on the simultaneous test of service quality variables, price perceptions, and costumer satisfaction have a significant effet on costumer loyalty whit an f count of 39,256 > f table of 2,87 whit a significance of 0,000 at Semet Barbershop Telagawaru Village Labuapi District.